The impact of the medical school admissions interview: A systematic review - Lin, John C; Shin, Christopher; Greenberg, Paul B (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Background: Interviews are considered an important part of the medical school admissions process but have been critiqued based on bias and reliability concerns since the 1950s. To determine the impact of the interview, this systematic review investigated the characteristics and outcomes of medical students admitted with and without interviews.Methods: We searched four literature databases from inception through August 2022; all studies comparing medical students admitted with and without interviews were included. We excluded studies from outside the medical school setting and non-research reports. We reviewed interview type, study design, quality, and outcomes.Results: Eight studies from five institutions across five countries were included. Six reported no demographic differences between students admitted with and without interviews; one found that more men were admitted without than with semi-structured interviews, and both cohorts had similar academic and clinical performance. Structured interviews admitted students who scored higher on clinical exams and social competence and lower on academic exams. Cohorts admitted with and without structured interviews had similar mental health issues by their final year of medical school.Discussion: This review suggests that students admitted with and without unstructured and semi-structured interviews were similar demographically, academically, and clinically. Moreover, structured interviews selected more socially competent students who performed better clinically but worse academically. Further research is needed to determine the impact of the selection interview in medical school admissions.